2008
DOI: 10.1016/j.ejmech.2007.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and antiproliferative activity of some 3-benzylidene-2,3-dihydro-1-benzopyran-4-ones which display selective toxicity for malignant cells

Abstract: A series of 3-benzylidene-4-chromanones 1a-l were prepared and their cytotoxicity towards human Molt 4/C8 and CEM T-lymphocytes as well as murine L1210 lymphoid leukemia cells were compared to the previously generated biodata in these three assays for the isosteric 2-benzylidene-1-tetralones 2a-l. Over 40% of the compounds in series 1 were more potent than their counterparts in series 2, while equipotency was noted in one-third of the comparisons made. In general the IC(50) values of 1a-l towards the human T-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 19 publications
2
51
1
Order By: Relevance
“…It is urgent to explore the method by which this type of side-effect can be alleviated. We also found that the introduction of dimethylamino groups [6,12] and chloride [8] in the 4'-position of benzene ring produced comparable TS values with [3,10,15]. This indicates that molecular shape, size and polarization are useful for the evaluation of tumor-specificity of 3-benzylidenechromanone derivatives.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…It is urgent to explore the method by which this type of side-effect can be alleviated. We also found that the introduction of dimethylamino groups [6,12] and chloride [8] in the 4'-position of benzene ring produced comparable TS values with [3,10,15]. This indicates that molecular shape, size and polarization are useful for the evaluation of tumor-specificity of 3-benzylidenechromanone derivatives.…”
Section: Discussionmentioning
confidence: 51%
“…This may be a new type of side-effect induced by anticancer drugs. We found that compounds [6,8,16] showed much lower cytotoxicity against human normal keratinocytes as compared with DXR and 5-FU (Table II). It is urgent to explore the method by which this type of side-effect can be alleviated.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The compounds in series 1 were prepared by a literature procedure 13 reported previously from our laboratory and the purity of the compounds was established by 1 H-NMR spectroscopy, melting points and elemental analyses while the synthesis of the analogs in series 2-5 has been described previously 14 .…”
Section: Synthesis Of Compoundsmentioning
confidence: 99%
“…Second, an ether oxygen atom was placed into the heterocyclic ring with a view to serving two purposes, namely, reducing the lipophilicity of the molecules and also having the capacity to assist the alignment of these compounds at a binding site by hydrogen bonding. Third, a previous study revealed that 1a-l displayed excellent cytotoxic properties towards several tumour cell lines and are well tolerated in mice 13 . As a part of our ongoing effort to develop novel anti-mycobacterial agents, the present investigation is focused on the evaluation of the antitubercular potential of 3-benzylidene-4-chromanones 1 and also to develop structure-activity relationships that would afford guidelines for expansion in this area of study.…”
Section: Introductionmentioning
confidence: 99%